Gender grading bias in junior high school mathematics - Petter Berg; Ola Palmgren; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2019)
Admission to high school in Sweden is based on the final grades from junior high. This paper compares students' final mathematics grade with new data from a high school introductory test score in mathematics. Both the grades and the test are based on the same syllabus, but teachers enjoy great discretion when deciding final grades, as the grades are not externally evaluated. The results show a substantial grading difference, consistent with grading bias against boys.
Keywords: I20; I24; I28; J16; 330; Educational economics; Gender; Grading bias; Mathematics